MENINGKATKAN HASIL BELAJAR IPS MENGGUNAKAN MEDIA GAMBAR MENGENAI KERAGAMAN SUKU BANGSA DAN BUDAYA DI INDONEISA - Suciarti, Indi (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
The problem in the classroom is the low learning outcomes of students social studies learning. Where to solve this problem researchers apply approach with image media so that it is expected to improve results learning fourth grade students of SD Sejahtera Way Kandis in social studies learning. Method The research used is classroom action research with a groove action planning, action, observation and reflection. Subject The research was the fourth grade students of SDN 2 Palembang. The material taught in the first cycle is various ethnic groups, and the second cycle is cultural diversity. Data collection was carried out in each cycle. The data collected in the form of qualitative data and quantitative data. Data collected in three ways, namely tests, observations, interviews. The results obtained on cycle I, namely from 20 students 14 students experienced completeness of learning with the percentage of classical completeness 70% and the percentage of classical absorption 77.75%, This result is still in the sufficient category so that there are still shortcomings that must be fixed. The results obtained in cycle II experienced increase, all students experience learning completeness, with a percentage 100% classical complete and 86% classical absorption. Average value teacher activity in cycle I is still in good category and cycle II is very good, and the average value of student activity in cycle I is sufficient and cycle II is located in either category. Based on predetermined indicators, it can be concluded that by using a group learning model student mastery of the material continues to increase so that it has an impact on increase in social studies learning outcomes for fourth grade students of SDN 2 Palembang.